Comparative genomic analysis reveals metabolic flexibility of Woesearchaeota - Wen-Cong Huang (Nature Portfolio, 2021)
The biology of the archaeal phylum Woesearchaeota is poorly understood due to the lack of cultured isolates. Here, the authors analyze datasets of Woesearchaeota 16 S rRNA gene sequences and metagenome-assembled genomes to infer global distribution patterns, ecological preferences and metabolic capabilities.